Transforming the Art of Fiction: Walter Besant, Professional Service and the Society of Authors - Richard Salmon (Cahiers Victoriens et Edouardiens)
Founded in 1884 by the novelist and historian Walter Besant (1836–1901), the Incorporated Society of Authors went on to become the most successful and long-lasting professional association organized by and for the benefit of authors in Britain. Established in the belief that collective action was necessary in order to defend authors’ ‘trade interests’ and to express a long-held ‘grievance’ against exploitative publishers and inadequate laws of copyright, the Society of Authors presents a valuable case-study of the wider transformation of the arts in modern professional society. Though Besant’s influence on the early development of the Society is well-documented, the conception of professional identity which shaped his activity during its first two decades remains under-explored. This essay considers two distinct, but interrelated, aspects of Besant’s work for the Society of Authors during this period. Firstly, it examines the various models of professional association and their functions, envisaged by Besant and other leading members of the Society, ranging from the pragmatic to the utopian. How did members of the Society conceive of its role in providing professional service in relation to the wider field of the literary market? Secondly, the essay explores the Society’s professional service in relation to the emerging genre of the literary manual—or ‘how to’ guide to professional authorship—, a connection which in 1884, the year of its official foundation, sparked a memorable debate on the ‘art of fiction’ between Besant and his fellow novelist, Henry James. In what ways was this well-known late-Victorian debate on the aesthetic and moral dimensions of the novel shaped by the formation of collective professional identities for authors?